3D Printables for Extended Reality - ALBU Răzvan-Daniel; MORGOȘ Florin Lucian; SIVU Mario; BITTENBINDER Maria (Journal of Electrical and Electronics Engineering, 2023)
This work aims to show how VR related components and accessories can be created using a 3D printer. VR accessories include audio/video systems, LCD glasses, “HMDs (Head Mounted Display), BOOMs (Binocular Omni-Orientation Monitor)”, exoskeletons, tracking devices, etc. It is widely admitted that VR will play a focal function in numerous fields, but there are also some barriers. Would it be plausible to develop a streamlined process and device, produced and implemented on a local site, cheaply and rapidly, to interact with VR already existing models? This research work goes into these questions and possible resolutions.